2003
DOI: 10.1002/pon.653
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes, knowledge, risk perceptions and decision‐making among women with breast and/or ovarian cancer considering testing for BRCA1 and BRCA2 and their spouses

Abstract: A limited number of studies have examined the involvement of spouses in the decision-making process for genetic testing as well as impact of the actual testing. This report presents data from 40 women with a personal history of breast and/or ovarian cancer who were considering genetic testing for BRCA1 and BRCA2 and their spouses. We examined knowledge and attitudes regarding genetic testing for breast cancer susceptibility, perceptions of the likelihood that their wives (the women) had a BRCA1 or BRCA2 mutati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
58
0
2

Year Published

2004
2004
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(63 citation statements)
references
References 31 publications
3
58
0
2
Order By: Relevance
“…This was not expected, given that prior studies showed increases in knowledge about cancer genetics following counseling. [7][8][9][10][11][12][13][14] Areas showing improvements in knowledge from pre-to post-counseling were mechanisms of cancer inheritance (increase), meaning of a positive result (increase), and practitioner knowledge (decrease). Yet, personal behavior, meaning of a negative result, and frequency of inherited cancer did not change as a result of genetic counseling.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This was not expected, given that prior studies showed increases in knowledge about cancer genetics following counseling. [7][8][9][10][11][12][13][14] Areas showing improvements in knowledge from pre-to post-counseling were mechanisms of cancer inheritance (increase), meaning of a positive result (increase), and practitioner knowledge (decrease). Yet, personal behavior, meaning of a negative result, and frequency of inherited cancer did not change as a result of genetic counseling.…”
Section: Discussionmentioning
confidence: 99%
“…Eight [7][8][9][10][11][12][13][14] of the 15 studies identified used the National Institutes of Health National Center for Human Genome Research Cancer Genetics Consortium knowledge scale, 7 an 11-item scale with a true/false response format. Topics included mechanisms of cancer inheritance, frequency of hereditary cancer, meaning of a positive result, and efficacy of cancer screening.…”
Section: Cancer Genetic Knowledge and Interest In Testingmentioning
confidence: 99%
“…For the UK, it has been reported that characteristics of counselees may be associated with their ability to bring up a positive family cancer history, or to ask questions about the possible hereditary aspects (Brain et al 2000;Wonderling et al 2001) and may thus play a role in initiating a referral. It has been shown that counselees who were referred for cancer genetic counseling and participated in studies on psychosocial aspects of counseling more often had a higher educational background, suggesting that less well-educated patients have less easy access to a family cancer clinic in the Netherlands (Pieterse et al 2006), the UK (Armstrong et al 2002) and the USA (Bluman et al 1999). Next to suboptimal referral of counselees willing to undergo genetic testing, some counselees eligible for genetic testing may decline referral.…”
Section: Introductionmentioning
confidence: 99%
“…Studies that have examined levels of breast cancer genetics knowledge among women with a family history of breast cancer (Lerman et al, 1996Hughes et al, 1997;Wonderlick and Fine, 1997;Cull et al, 1998;Bluman et al, 1999;Donovan and Tucker, 2000) have found wide variation in knowledge about many facets of genetic testing, including the cancer risks associated with different genes and different mutations and the effectiveness of interventions, for example screening, chemoprevention, or surgery for reducing risk (Geller et al, 1997;Audrain et al, 1998;Bluman et al, 1999).…”
mentioning
confidence: 99%